(untitled) (Bulletin of Innovative Research, 2026)
This study presents an updated analysis of the taxonomic structure and species diversity of longhorn beetles (Coleoptera: Cerambycidae) in Uzbekistan. Based on international databases, published literature, and field surveys conducted between 2011 and 2023, a total of 86 species and subspecies belonging to 6 subfamilies, 20 tribes, 34 genera, and 23 subgenera were recorded. The subfamilies Lamiinae and Cerambycinae were found to be dominant in terms of species richness. The results contribute to a better understanding of the taxonomic composition of the entomofauna of Uzbekistan and provide a scientific basis for biodiversity assessment and monitoring of dendrophagous and xylophagous pest species.